Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1021/ja0621997
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study on the Palladium-Catalyzed Allylation of Primary Amines by Allylic Alcohol

Abstract: The palladium-catalyzed allylation of primary amines has been investigated by DFT calculations (B3PW91, PCM method), and two potential mechanisms were studied. The first mechanism relies on the formation of cationic hydridopalladium complexes. Their formation involves a metal-assisted formal (1,3) shift of a proton from the nitrogen atom of an ammonium to the Cbeta carbon atom. The second part of the cycle relies on a ligand exchange through a pentacoordinated 18VE hydridopalladium complex. The last step likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 52 publications
(35 reference statements)
5
42
0
Order By: Relevance
“…Ozawa and co-workers reported the first examples in which allylic alcohols were directly used as coupling partners in Pd-catalyzed allylic substitution reactions by the π-allyl palladium complexes of substituted diphosphinidenecyclobutene ligands (DPCB-Y) [15]. Mechanistic studies demonstrated that C-O bond dissociation is the rate-determining step in these reactions (proposed by Ozawa and Yoshifuji to proceed via a palladium-hydride intermediate) [20], which was later also confirmed by le Floch and co-workers on the basis of DFT calculations (invoking ammonium promoted protonation of the allyl alcohol) [21]. The theoretical study further showed that nucleophilic attack on the π-allyl complex first generates a cationic allyl amine, which assists in dissociation of the hydroxyl group in the oxidative addition step.…”
Section: Introductionmentioning
confidence: 74%
“…Ozawa and co-workers reported the first examples in which allylic alcohols were directly used as coupling partners in Pd-catalyzed allylic substitution reactions by the π-allyl palladium complexes of substituted diphosphinidenecyclobutene ligands (DPCB-Y) [15]. Mechanistic studies demonstrated that C-O bond dissociation is the rate-determining step in these reactions (proposed by Ozawa and Yoshifuji to proceed via a palladium-hydride intermediate) [20], which was later also confirmed by le Floch and co-workers on the basis of DFT calculations (invoking ammonium promoted protonation of the allyl alcohol) [21]. The theoretical study further showed that nucleophilic attack on the π-allyl complex first generates a cationic allyl amine, which assists in dissociation of the hydroxyl group in the oxidative addition step.…”
Section: Introductionmentioning
confidence: 74%
“…The synthetic importance of this process prompted us to investigate the reaction mechanism. [15] We carried out DFT calculations [16] for the CÀO bond cleavage of allyl alcohol with the help of methanol (Figure 1). The results suggest that the cleavage of the stable CÀO bond can be easily achieved in methanol through hydrogen-bond activation.…”
Section: Methodsmentioning
confidence: 99%
“…The calculated catalytic cycle is somewhat related to the mechanism proposed for the palladium-catalyzed process, [35] yet differs from it by the ligand-exchange step (Scheme 12). Indeed, it involves an associative mechanism with formation of an 18-VE platinum complex with two h 2 -coordinated olefins, whereas in the case of palladium, it involves the formation of a 14-VE complex by a dissociative mechanism.…”
mentioning
confidence: 85%
“…[6] Efficient catalysts featuring palladium [7][8][9][10][11][12][13][14][15][16] and iridium, [17,18] were devised but in most cases the presence of an activator (usually a Lewis acid) was still needed to facilitate departure of the OH group. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Two years ago, we reported on a complete mechanistic study of the allylation of primary amines catalyzed by palladium(0) complexes, [35] and we showed that the use of a significant amount of Lewis acid (at least in the case of palladium) is not a prerequisite provided that the ligands employed display a strong p-accepting capacity to facilitate the release of substrates from the intermediate 16-valence-electron(VE) complexes, and that traces (7), which was structurally characterized and appears to be a catalytic intermediate. A DFT study showed that the mechanism of the platinum-catalyzed allylation of amines with allyl alcohols differs from the palladium-catalyzed process, since it involves an associative ligand-exchange step involving formation of a tetracoordinate 18-VE complex.…”
Section: Introductionmentioning
confidence: 99%